Etiek as optiek? Oor die rol van beelde en verbeelding in die Christelike morele lewe. - Vosloo, R (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
Ethics as optics? On the role of images and imagination in the Christian moral life This article investigates the relationship between ethics and imagination. After arguing that a reappraisal of this relationship requires a critique of certain methodological presuppositions of modernistic ethical theories, the importance of discerning between idol and icon in “an age of the image” is highlighted. Such discernment is connected closely with the character or identity of the moral person and community. Hence the article proceeds by reclaiming some notions from virtue theory. The role that communal practices play in the transformation of Christian imaginations also receives emphasis. Moreover, it is argued that Christian understandings of imagination find deep meaning and motivation through the participation, in Christ and through the Spirit, in the life of the triune God.